Potential drug–drug interactions between antiretroviral drugs and comedications, including dietary supplements, among people living with HIV: A clinical survey. Issue 1 (6th May 2022) - Tinggaard, Michaela; David, Kim Peter; Gerstoft, Jan; Hansen, Ann‐Brit Eg; Kirk, Ole; Lebech, Anne‐Mette; Lindhardt, Bjarne Ørskov; Rose, Michala Vaaben; Ryom, Lene; Weis, Nina; Benfield, Thomas
Abstract: Objective: Age‐related comorbidities, polypharmacy and thereby the risk of potential drug–drug interactions (PDDIs) among people living with HIV (PLWH) have increased over the years. We estimated the prevalence of comedications, including dietary supplements, and evaluated PDDIs among PLWH receiving antiretroviral therapy (ART) in Denmark in an outpatient setting. Methods: Information on prescription medication, over‐the‐counter medication and dietary supplements was obtained from adult PLWH receiving ART attending two outpatient clinics in Denmark. The PDDIs were identified using the University of Liverpool's drug interaction database. Associations between PDDIs and relevant variables were compared using logistic regression models. Results: A total of 337 PLWH receiving ART with a median age of 53 years (interquartile range: 45–61) were included; 77% were male and 96% had a HIV‐RNA viral load < 50 copies/mL. Twenty‐six per cent of participants received five or more comedications and 56% consumed dietary supplements. Co‐administration of drugs requiring dose adjustment or monitoring was identified in the medication lists of 52% of participants, and 4.5% were on drugs that should not be co‐administered. Male sex [odds ratio (OR) = 1.9, 95% confidence interval (CI): 1.0–3.4], being on a protease inhibitor (OR = 4.3, 95% CI: 1.9–9.7), receiving five or more comedications (OR = 3.3, 95% CI: 1.5–7.2), taking over‐the‐counter medications (OR = 1.9, 95% CI: 1.1–3.3) and dietary supplements (OR = 2.0, 95% CI: 1.2–3.3) were independent predictors of PDDIs. Conclusion: Potential drug–drug interactions were common among our study population Our study confirms that polypharmacy and being on a protease inhibitor‐based regimen increase the risk of PDDIs considerably and highlights the importance of questioning PLWH about dietary supplement intake.